Predicting 90-Day Outcome After Thrombectomy: Baseline-Adjusted 24-Hour NIHSS Is More Powerful Than NIHSS Score Change. Issue 8 (August 2021) - Mistry, Eva A.; Yeatts, Sharon; de Havenon, Adam; Mehta, Tapan; Arora, Niraj; De Los Rios La Rosa, Felipe; Starosciak, Amy K.; Siegler, James E.; Mistry, Akshitkumar M.; Yaghi, Shadi; Khatri, Pooja
Abstract : Background and Purpose: The National Institutes of Health Stroke Scale (NIHSS) measured at an early time point is an appealing surrogate marker for long-term functional outcome of stroke patients treated with endovascular therapy. However, definitions and analytical methods for an early NIHSS-based outcome measure that optimize power and precision in clinical studies are not well-established. Methods: In this post-hoc analysis of our prospective observational study that enrolled endovascular therapy-treated patients at 12 comprehensive stroke centers across the US, we compared the ability of 24-hour NIHSS, ΔNIHSS (baseline minus 24-hour NIHSS), and percentage change (NIHSS×100/baseline NIHSS), analyzed as continuous and dichotomous measures, to predict 90-day modified Rankin Scale (mRS) using logistic regression (adjusted for age, baseline NIHSS, glucose, hypertension, Alberta Stroke Program Early CT Score, time to recanalization, recanalization status, and intravenous thrombolysis) and Spearman ρ. Results: Of 485 patients in the BEST (Blood Pressure After Endovascular Stroke Therapy) cohort, 446 (92%) with 90-day follow-up data were included. An absolute 24-hour NIHSS, adjusted for baseline in multivariable modeling, had the highest predictive power of all definitions evaluated (aR 2 0.368 and adjusted odds ratio 0.79 [0.75–0.84], P <0.001 for mRS score 0–2; aR 2 0.444 and adjusted odds ratio 0.84 [0.8–0.86] for ordinal mRS). For predicting mRS score of 0–2 with a cut point, the second most efficient approach, the optimal threshold for 24-hour NIHSS score was ⩽7 (sensitivity 80.1%, specificity 80.4%; adjusted odds ratio 12.5 [7.14–20], P <0.001), followed by percent change in NIHSS (sensitivity 79%, specificity 58.5%; adjusted odds ratio 4.55 [2.85–7.69], P <0.001). Conclusions: Twenty-four–hour NIHSS, adjusted for baseline, was the strongest predictor of both dichotomous and ordinal 90-day mRS outcomes for endovascular therapy-treated patients. A dichotomous 24-hour NIHSS score of ⩽7 was the second-best predictor. Although ΔNIHSS, continuous and dichotomized at ≥4, predicted 90-day outcomes, absolute 24-hour NIHSS definitions performed better. Abstract : Supplemental Digital Content is available in the text.